Textual and Literary Criticism of the Books of Kings : Collected Essays - Barrera, Julio Trebolle, (Vetus Testamentum, Supplements;, 2020)
This volume contains a collection of the author's life-long study (along with some new research written specifically for this book) of the text of 1-2 Kings, some of them translated into English for the first time. Julio Trebolle's career has focused on the history of these biblical books from the triple angle of a combined textual, literary and source-compositional criticism. His usage of the Septuagint and its secondary versions like the Old Latin as a basis for the reconstruction of the history of the text is an invaluable contribution to the panorama of textual pluralism in the Bible during the Second Temple period which has emerged after the discoveries of the Dead Sea.